2022
DOI: 10.2478/ata-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Data from Robotic Milking Regarding to Heat Stress of Dairy Cows

Abstract: The paper presented is dedicated to investigation of the temperature-humidity index (THI) and its impacts on the performance parameters of dairy cattle. These parameters were recorded at four farms in the central Slovakia; the experiments took place three years. These parameters comprised milking time, time spent in the milking box, and connection time. The THI was calculated according to the standard formula and individual periods were established on the basis of achieved THI values. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…the effect of high temperature and humidity on the cow welfare and performance. Bodo et al (2022) and Osei-Amponsah et al (2020) found a positive correlation between the heat stress and a reduction in milking time and time spent in the milking box, and in general cows’ welfare. Therefore, the performance of robotic milking systems could easily be improved by simply providing shade and water for cows to cool down during hot months.…”
Section: Discussion Of Applications Of Dairy 40 Technologies In Milk ...mentioning
confidence: 94%
“…the effect of high temperature and humidity on the cow welfare and performance. Bodo et al (2022) and Osei-Amponsah et al (2020) found a positive correlation between the heat stress and a reduction in milking time and time spent in the milking box, and in general cows’ welfare. Therefore, the performance of robotic milking systems could easily be improved by simply providing shade and water for cows to cool down during hot months.…”
Section: Discussion Of Applications Of Dairy 40 Technologies In Milk ...mentioning
confidence: 94%